THE INFLUENCE OF READING INTEREST ON LEARNING ACHIEVEMENT AT STUDENT - Nuraini; Dea Ananda Safitri; Varin Gusti Andini; Upik Apriyanti (CV. Doki Course and Training, 2023)
This study aims to determine the effect of reading interest on learning achievement in 4th semester students of the Faculty of Psychology at UIN Raden Fatah Palembang. This study used a survey method with purposive sampling of 30students.Data were collected using a reading interest questionnaire and student learning achievement scores. Data analysis was conducted using simple linear regression analysis. The results showed that reading interest has a significant influence on the learning achievement of students of the Faculty of Psychology at UIN Raden Fatah Palembang. The correlation value or relationship between the two variables, namely the independent variable (Reading Interest) and the dependent variable (Learning Achievement), which is indicated by the R value of 0.751. In addition, R Square has a value of 0.565. The significance value shows the F Count value of 36, 330 with a significance level of 0.000 <0.05, which indicates that the effect of the independent variable on the dependent variable is 5.65%. The regression analysis results show that there is a positive relationship between reading interest and student learning achievement. The higher a person's reading interest, the higher their learning achievement. The implication of this study is that to improve students' learning achievement, it is necessary to increase their reading interest. This research can be a contribution to the development of higher education in Indonesia, especially in an effort to improve the quality of learning at the Faculty of Psychology at UIN Raden Fatah Palembang.